Introduction to Islamic Education Values through the Art of Wayang Thengul - Abdul Khamid; M. Miftakhul Huda; Abdulloh Safiq; Chalifah Chalifah (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
Wayang Thengul is a traditional art form unique to Bojonegoro, East Java, featuring three-dimensional puppetry accompanied by gamelan music. This study aims to explore the Islamic educational values embedded in Wayang Thengul performances and understand its role as a medium for dakwah and the preservation of local culture. The research uses a qualitative method with a phenomenological approach, involving a literature review, direct observation, and semi-structured interviews with the lead puppeteer, Pak Darno. The findings reveal that Wayang Thengul functions not only as entertainment but also as an educational medium conveying Islamic values such as etiquette, gratitude, trust in God, patience, and steadfastness. Through stories of Islamic figures and legendary tales, the performance effectively introduces social and religious values to the community. Innovations, such as the inclusion of modern musical instruments, have enhanced Wayang Thengul's appeal to younger generations. Wayang Thengul plays a significant role in preserving traditional art while strengthening character education and the spiritual development of the community